Association between polymorphisms of MIR17HG and risk of colorectal cancer in the Chinese Han population. Issue 6 (3rd April 2019) - Chen, Peng; Bai, Yuwei; Li, Yaru; Yuan, Yuemin; Cheng, Yimin; Pang, Jianjian; Zhu, Hongli; Chen, Chao
Abstract: Background: Colorectal cancer is the third most common cancer worldwide. Recently, an increasing number of evidences suggest that genetic susceptibility plays an important role in the occurrence of colorectal cancer. This study aimed to better understand the influence of MIR17HG polymorphisms on colorectal cancer susceptibility in the Chinese Han population. Methods: We recruited 514 patients with colorectal cancer and 510 healthy controls to investigate the association between polymorphisms of MIR17HG and risk of colorectal cancer in the Chinese Han population. Genotyping was performed with the Agena MassARRAY platform. We used the χ 2 test to compare the distributions of single nucleotide polymorphisms (SNPs) allele and genotypes frequencies between cases and controls. Odds ratios and 95% confidence intervals were calculated by logistic regression analysis to evaluate the association under genetic models. Linkage disequilibrium between the five SNPs was assessed using the Haploview software. Results: Overall analysis found that rs7336610 and rs1428 and haplotype CTAGA were significantly associated with increased risk of colorectal cancer. However, we found rs7318578 was associated with a decreased risk of colorectal cancer in the dominant model. Stratification analysis showed that rs7336610, rs7318578, and rs1428 were also associated with rectal cancer risk. Gender stratification analysis found that rs7336610, rs7318578, rs17735387, and rs1428 were significantly associated with colorectal cancer risk in males. Conclusion: In conclusion, this study indicated that the polymorphisms of MIR17HG were associated with colorectal cancer risk. Therefore, our findings may provide new insights into the development of colorectal cancer. Further association and functional studies are of great importance to confirm these results and to define the potential biological mechanism of colorectal cancer. Abstract : We recruited 514 patients with colorectal cancer and 510 healthy controls to investigate the association between polymorphisms of MIR17HG and risk of colorectal cancer in the Chinese Han population. Overall analysis and stratification analysis found that rs7336610, rs7318578, rs17735387, and rs1428 were significantly associated with colorectal cancer risk. Therefore, our findings may provide new insights into the development of colorectal cancer.